Analisis Pembiayaan Sekolah Gratis (Studi Kasus SMK Dhuafa Padang) - Yahya Yahya; Hadiyanto Hadiyanto; Sri Mures Walef; Nikmatulaili Nikmatulaili (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
The purpose of this research is to find out the sources of funds, planning, planning and evaluation carried out by SMK Dhuafa Yayasan Bina Nusantara. This research uses a qualitative approach with a case study type of research conducted at SMK Dhuafa Yayasan Bina Nusantara. The results of the research include sources of school funding coming from the government, related parties through infaq and sadakah institutions and foundations as permanent donors. Planning activities refer to the RABPY which is made before the learning activities take place. Funding expenditures include payment of honorariums for teachers and teaching staff, maintenance of buildings and facilities and infrastructure that support student learning activities, then evaluation is carried out by the foundation together with the school principal by making activity accountability reports. In conclusion, the Dhuafa Vocational School of the Bina Nusantara Foundation in running the free school program has been implemented well without collecting a penny of funding from students. Keywords: Funding, Free School